a+b=166
(a:3)+(b:4)=48
Răspunsuri la întrebare
Răspuns de
0
a+b=166 => a=166-b
a/3 +b/4=48(aducem la acelasi numitor:12)
4a/12+3b/12 =48*12/121 (eliminam numitorii acum)
4a+3b=576
4(166-b)+ 3b=576
664 - 4b+ 3b=576
664 - b =576
b=88
a=166-b
a=166-88=78
a/3 +b/4=48(aducem la acelasi numitor:12)
4a/12+3b/12 =48*12/121 (eliminam numitorii acum)
4a+3b=576
4(166-b)+ 3b=576
664 - 4b+ 3b=576
664 - b =576
b=88
a=166-b
a=166-88=78
Alte întrebări interesante
Fizică,
9 ani în urmă
Engleza,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă